2016
DOI: 10.1007/s12565-016-0336-z
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin ameliorates peripheral nerve ischemia–reperfusion injury through the NF-kappa B pathway

Abstract: This study aimed to investigate the protective effect of quercetin against ischemia-reperfusion (IR) injury induced in the sciatic nerve of the rat. Quercetin (20 mg/kg) was given during ischemia just before reperfusion. Four groups of rats (Q+IR3, Q+IR7, Q+IR14, and Q+IR28) received 3, 7, 14, and 28 days of reperfusion, respectively, after the intraperitoneal injection of quercetin. After reperfusion, a behavioral test was performed and the sciatic functional index was calculated. Each sciatic nerve was stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Bcl-2-associated × protein expression, caspase-3 and caspase-9 activation and levels of p53 mRNA, a protein that regulates the cell cycle, increased significantly in a dose-dependent manner in neuroblastoma cells taken from mice administered with quercetin ( 58 ). Gholami et al ( 59 ) reported that quercetin may be beneficial in the treatment of sciatic ischemic/reperfusion injury due to its anti-apoptotic and anti-inflammatory effects and its ability to reduce the expression of nuclear factor-κB. In the present study, the AI in Schwann cells following sciatic nerve damage was significantly increased the T-7 and T-28 groups compared with the S-7 and S-28 groups, respectively.…”
Section: Discussionsupporting
confidence: 55%
“…Bcl-2-associated × protein expression, caspase-3 and caspase-9 activation and levels of p53 mRNA, a protein that regulates the cell cycle, increased significantly in a dose-dependent manner in neuroblastoma cells taken from mice administered with quercetin ( 58 ). Gholami et al ( 59 ) reported that quercetin may be beneficial in the treatment of sciatic ischemic/reperfusion injury due to its anti-apoptotic and anti-inflammatory effects and its ability to reduce the expression of nuclear factor-κB. In the present study, the AI in Schwann cells following sciatic nerve damage was significantly increased the T-7 and T-28 groups compared with the S-7 and S-28 groups, respectively.…”
Section: Discussionsupporting
confidence: 55%
“…Several limitations are acknowledged in our study. First, quercetin has a wide variety of sites of action including PI3K/Akt, [ 40 ] NF-κB [ 41 ] and estrogen receptor, [ 42 ] and it is difficult to exclude the involvement of such other mechanisms. For example, because activated PI3K/Akt/mTOR pathways are known to induce corticosteroid insensitivity, [ 9,10 ] quercetin could restore corticosteroid insensitivity also via that pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral nerve damage leads to microvascular damage, which can lead to the formation of free oxygen free radicals and lipid peroxidation [23]. The formation of free radicals can accelerate tissue damage and induce oxidative stress [24]. In the present study, Schwann cells underwent pronounced phagocytic transformation, which is an indicator of the natural healing process.…”
Section: Discussionmentioning
confidence: 52%